PENERAPAN METODE KNOW–WANT TO KNOW–LEARNED (KWL) DALAM MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS IV SD PADA PEMBELAJARAN BAHASA INDONESIA - Diniati; Setiawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low reading comprehension skills of fourth-grade students at SD Negeri 1 Blang Mangat in Indonesian language learning. The students experienced difficulties in identifying important information, answering questions based on the reading texts, and drawing conclusions from the texts they had read. This study aimed to describe the implementation of the Know-Want to Know-Learned (KWL) method and to determine the improvement in students’ reading comprehension skills after the implementation of the method. The study employed a qualitative approach using Classroom Action Research (CAR) based on the Kemmis and McTaggart model, which consists of planning, action, observation, and reflection stages. The research was conducted in two cycles involving 29 fourth-grade students as the research subjects. Data were collected through observations, tests, and interviews. The data were analyzed through data reduction, data display, and conclusion drawing. The findings revealed that the implementation of the KWL method improved teacher activities, student activities, and students’ reading comprehension skills. Teacher activity increased from 80.00% in Cycle I to 95.33% in Cycle II, while student activity increased from 74.66% to 92.66%. Students’ classical learning mastery also improved from 40.00% in Cycle I to 87.50% in Cycle II. Therefore, the Know-Want to Know-Learned (KWL) method is effective in improving the reading comprehension skills of fourth-grade students in Indonesian language learning.